Rasch model: kemampuan literasi matematis siswa SMA negeri di kota Bogor berdasarkan kategori adversity quotient - Sitta Agustiani; Leni Marlena (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this research is to determine the mathematical literacy skills of high school students in Bogor City based on their Adversity Quotient (AQ) categories. The sample was selected using Purposive Sampling technique, consisting of 412 eleventh-grade students from public high schools in Bogor City. The research method employed was descriptive quantitative to depict the mathematical literacy abilities according to students' AQ categories. Data collection was conducted through the distribution of an AQ questionnaire and four sets of mathematical literacy tests related to the topics of sequences and series. The data analysis technique used in this study was the Rasch Model with Winstep version 3.73. The results of the item-person map divided the 11th-grade students from public high schools in Bogor City into five categories of mathematical literacy abilities, and within each category, their corresponding AQ categories were also examined. Based on the analysis, it can be concluded that the eleventh-grade students from public high schools in Bogor City are predominantly characterized by low mathematical literacy ability, with the AQ category of transitional quitter-camper.